Effect of pre-heating temperature on the characteristics of PZT thin films grown by using a triol sol-gel route - Sarawut Thountom (2018)
Lead zirconate tilanate (PZT) films with compositions near the morphotropic phase boundary were fabricated on Pt(111)/Ti/SiO2/Si(100) using the triol sol-gel method. The effect of the pre-heating temperature on the phase transformations, microstructures, electrical properties, and ferroelectric properties of the PZT thin films was investigated. Randomly oriented PZT thin films pre-heated at 400°C for 10 min and annealed at 600°C for 30 min showed well-defined ferroelectric hysteresis loops with a remnant polarization of 26.57 μC/cm2and a coercive field of 115.42 kV/cm. The dielectric constant and dielectric loss of the PZT films were 621 and 0.0395, respectively. The microstructures of the thin films are dense, crack-free, and homogeneous with fine grains about 15-20 nm in size. © World Scientific Publishing Company.